Exploring the Evidence of and Barriers to Implementation of Customer Relationship Management in Small Accommodation Enterprises. of Drenthe, Netherlands - Oudshoorn-Fuller, Melissa M (2012)
Micro tourism accommodation businesses face increasing challenges to attract and keep customers. Literature suggests that developing a strong relationship with customers and a strategic approach to managing customer relationships provides opportunities for businesses to both increase loyalty and generate new business.